DEVELOPING EVALUATION INSTRUMENT OF READING FOUR TEST FOR UNIVERSITY STUDENT - Refai Refai (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2014)
Abstract: The objective of the study was to develop the evaluation Instrument of reading four test . The development of such instrument is a valuable effort to measure the students’ mastery of the reading skill and to improve the quality of the evaluation instrument which is produced by the teacher. Before the teacher develop the reading evaluation instrument, he had cultivated the previous test instrument to analyze the weakness and the strength of the implemented test instrument. After that, the teacher started to develop a prototype which has been modified by the teacher himself. Then, he administered the first try out to the English students of semester VII and collecting some inputs and critics of the modified reading test instrument after the students finished doing the test. The result of the test together with the students’ critics and inputs were used to rebuild the reading test intrument better. At last, the teacher has developed the evaluation instrument of reading test for students of semester VII in Muhammadiyah University of Metro.